Single versus repeated exposure to human polarized intestinal epithelial monolayers for in vitro protein hazard characterization. (October 2019) - Lanter, B.B.; Eaton, A.D.; Roper, J.M.; Zimmermann, C.; Delaney, B.; Hurley, B.P.
Abstract: Recent studies suggest human-derived intestinal epithelial cell (IEC) lines cultured as polarized monolayers on permeable Transwell ® filters are effective at differentiating between hazardous and non-hazardous proteins following a single exposure. In this study, IEC polarized monolayers were subjected to hazardous or non-hazardous proteins in nine exposures over 30 days and compared to a single exposure of the same protein. The objective was to evaluate whether repeated exposures to a protein differently alter barrier integrity or compromise cell viability compared to single exposures. Proteins tested included Clostridium difficile toxin A, Streptolysin O, Wheat Germ Agglutinin, Phaseolus vulgaris Hemagglutinin-E, bovine serum albumin, porcine serum albumin, and fibronectin. Evidence of diminished barrier integrity and/or cell viability following exposure to hazardous proteins was more pronounced in magnitude when IECs were subjected to multiple rather than single exposures. In some cases, an effect on IEC monolayers was observed only with repeated exposures. In general, IEC responses to non-hazardous proteins following either single or repeated exposures were minimal. Results from these studies support the utility of using cultured human IEC polarized monolayers to differentiate between hazardous and non-hazardous proteins and suggest that repeated exposures may reveal a greater magnitude of response when compared to single exposures. Highlights: Non-hazardous proteins had minimal effects on IECs irrespective of exposure frequency. Hazardous proteins had adverse effects on IECs after single and repeated exposures. The number and magnitude of hazard indices were increased with repeated exposures. A single exposure was sufficient to identify a hazardous protein.